Introducing CS to Newcomers, and JES As a Teaching Tool. - Barr, Valerie; Guzdial, Mark (Communications of the ACM, 2016)
The article discusses teaching computer science to Science and Technology Entry Program students at Union College's Kenney Community Center and the benefits of Jython Environment for Students, the text editing software for Python programming language. Topics include the use of a visual perception card game to analyze how human's solve problems versus how to program computers to solve problems, data representation inside computers, and the use of JES to facilitate programming in Media Computation.